Exposure and health risk assessment of deoxynivalenol among pregnant women in Wuhan - YAN Yizhong; LI Yanan; SONG Wenjing; ZHANG Zhen; LI Yiling; YANG Xuefeng; HAO Liping; WEI Sheng (Zhongguo shipin weisheng zazhi, 2021)
ObjectiveAs one of the common mycotoxins in the food, deoxynivalenol (DON) poses multiple health risks. Limited information is available on DON exposure in Chinese pregnant women who they are vulnerable to various pollutants exposure hazards. The purpose of this study was to detect urine DON concentrations and estimate dietary DON intake in Chinese pregnant women, and provide evidence for assessing the risk of dietary DON exposure for pregnant women.MethodsThe study involved 103 pregnant women from the Tongji birth cohort study in Wuhan, China. Urine samples were collected and dietary investigation was conducted using food-frequency questionnaire (FFQ). The level of DON in urine was determined by ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS).ResultsAmong 103 pregnant women, total DON was detected in 95 urine samples (92.23%, 95/103), free DON was detected in 76 samples (73.79%, 76/103). The mean total DON levels were 19.12 ng/mg creatinine for both trimesters, 15.17 ng/mg creatinine for the first trimester and 20.91 ng/mg creatinine for the second trimester. The dietary DON intake for pregnant women was 0.45-0.89 μg/(kg b. w.·d). The dietary DON intake of 11.65%-22.33% pregnant women exceeded current guidance regarding the provisional maximum tolerable daily intake (PMTDI) for DON. The diet of pregnant women was mainly rice and its products, and its intake was positively correlated with the concentration of DON.ConclusionIn this study, the detection rate of DON in the urine samples of pregnant women in Wuhan was high, but the level of DON was low. Future attention should be paid to the exposure level of pregnant women to DON and the potential health risks to both mother and fetus.